Etika Bisnis dalam Islam “Analisis perbandingan antara prinsip etika bisnis Islam dan konsep (Corporate Social Responsibility)” - Khaerul, Khaerul (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
This study discusses business ethics from an Islamic perspective as a strong foundation for building sustainable and responsible management. By conducting a comparative analysis between the principles of Islamic business ethics and the concept of Corporate Social Responsibility (CSR), the study demonstrates that Islamic values offer a holistic framework encompassing spiritual, social, and environmental dimensions. The research employs a literature review method with a qualitative-descriptive approach. The analysis reveals that Islamic business ethics not only promote individual ethical behavior but also advocate for a management system that is accountable to society and the broader natural environment.